1981
DOI: 10.2183/pjab.57.351
|View full text |Cite
|
Sign up to set email alerts
|

L-threo-3,4-dihydroxyphenylserine treatment for akinesia and freezing of Parkinsonism.

Abstract: Recent medical treatment of Parkinson's disease (PA) has been focused mainly on how to compensate dopamine (DA) deficiency in the striatum efficiently by using L-DOPA with/without peripheral DOPA-decarboxylase inhibitor. Norepinephrine (NE) has been also known as lowered in parkinsonism since start of pharmacological study around 1960. Marked decrease of dopamine-~3-hydroxylase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 0 publications
2
55
0
1
Order By: Relevance
“…Initial experience with L -DOPS treament which was initiated for the improvement of gait apraxia was promising (Narabayashi et al , 1984(Narabayashi et al and 1986Kondo, 1984;Ogawa et al 1984;Suzuki et al 1984a). In addition, L -DOPS was found to be effective for disease conditions other than parkinsonism and for symptoms other than gait apraxia, such as: juvenile form of parkinsonism ; familial amyloid polyneuropathy (Suzuki et al 1980(Suzuki et al , 1981(Suzuki et al and 1982 ; pure akinesia (Itou ji et al 1984;Yamamoto and Ujike, 1985;Narabayashi et al 1986) ; Shy-Drager's syndrome (Sakoda et al 1985) and neoplasm in the caudate head (Suzuki et al 1984b). Symptoms which responded to L -DOPS include ; gait apraxia ; freezing of speech and writing; depressive state; orthostatic hypertension (Suzuki et al 1981;Birkmayer et al 1983;Sakoda et al 1985) ; up and down phenomenon; L -DOPA induced apraxia and other symptoms of parkinsonism (Kondo, 1984).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial experience with L -DOPS treament which was initiated for the improvement of gait apraxia was promising (Narabayashi et al , 1984(Narabayashi et al and 1986Kondo, 1984;Ogawa et al 1984;Suzuki et al 1984a). In addition, L -DOPS was found to be effective for disease conditions other than parkinsonism and for symptoms other than gait apraxia, such as: juvenile form of parkinsonism ; familial amyloid polyneuropathy (Suzuki et al 1980(Suzuki et al , 1981(Suzuki et al and 1982 ; pure akinesia (Itou ji et al 1984;Yamamoto and Ujike, 1985;Narabayashi et al 1986) ; Shy-Drager's syndrome (Sakoda et al 1985) and neoplasm in the caudate head (Suzuki et al 1984b). Symptoms which responded to L -DOPS include ; gait apraxia ; freezing of speech and writing; depressive state; orthostatic hypertension (Suzuki et al 1981;Birkmayer et al 1983;Sakoda et al 1985) ; up and down phenomenon; L -DOPA induced apraxia and other symptoms of parkinsonism (Kondo, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, new agents to counteract each deficiency are now being introduced Narabayashi, 1985). L -threo -3, 4 -dihyd roxyphenylserine (L -DOPS) is a precursor of noradrenaline (Corrodi and Fuxe, 1967;Creveling et al 1968;Suzuki et al 1980Suzuki et al , 1982Suzuki et al , 1984Suzuki et al and 1985Edwards and Rizk, 1981;Edwards and Sedlock, 1982;Tanaka and Nishino, 1985). Based on the possible link between noradrenaline deficient state in the central nervous system (CNS) and akinetic symptoms, L -DOPE can be expected to counteract particularly gait related akinesia such as gait apraxia, festination and retropulsion, and possibly other forms of akinesia, all of which are most often noted in patients who had long been on L-DOPA treatment and extremely difficult to control because they are usually ref ractile to L -DOPA treatment (Narabayashi and Nakamura, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) reported that L threo-DOPS was effective in treating some symptoms of parkinsonism such as akinesia and freezing. Since degeneration of the noradrenaline-containing neurons in the LC concomitantly with degeneration of dopa minergic neurons in the substantia nigra was observed in patients with parkinsonism (7,8), the effects of L-threo-DOPS are considered to be due to supplemental noradrenaline in the brain.…”
mentioning
confidence: 99%
“…It has also been reported that L-DOPS produced a positive chronotropic effect in rat atrial preparations (5) as well as an inotropic effect in open-chest rats (6), a slow onset and long-lasting hypertensive effect in rats (7) and a diuretic effect in rats and mice (8). In clinical studies, DL or L DOPS has recently been reported to improve postual hypotension and dizziness in par kinsonian patients (9), and the patients with familial amyloid polyneuropathy (10) or Shy Drager syndrome (11), and also to show beneficial effect on akinesia or freezing phenomenon in advanced parkinsonian patients (12). In the present study, the effect of L-DOPS on the cerebral blood flow (CBF) was studied in rats in comparison with that of NE.…”
mentioning
confidence: 99%